Granulomatous Lung Disease Requiring Mechanical Ventilation Induced by a Single Application of Oxaliplatin-Based Chemotherapy for Colorectal Cancer: A Case Report - Wildner, Dane (Hindawi Publishing Corporation, 2013)
Combined chemotherapeutic regimens in conjunction with oxaliplatin are considered safe and effective treatment options in the clinical management of metastatic colorectal cancer. A 62-year-old male patient with a metastatic rectal carcinoma developed a pulmonary reaction after the first application of the combined standard chemotherapy regimen (5-fluorouracil and sodium folinic acid as a 24 h infusion and oxaliplatin). Following the first dose of chemotherapy, the patient developed acute dyspnoea and fever. A computerised scan of the chest revealed bilateral pulmonary patchy consolidation. Despite high-dose empiric antibiotic and antimycotic treatment, no clinical improvement was seen. The patient's condition deteriorated, and he required invasive mechanical ventilation. Diagnostic thoracoscopic wedge resections were performed for further diagnosis. The histological workup revealed distinct granulomatous inflammation, but no microbial pathogens were to be found. Thereupon, a drug-induced reaction to chemotherapy was suspected and high-dose steroid treatment initiated. Subsequently, the patient's respiratory condition improved and he was extubated. The present case exemplifies the rare course of a bilateral pneumonia-like, drug-induced granulomatous reaction following a single application of oxaliplatin. In addition to the known side effects of oxaliplatin-containing combination chemotherapy, unexpected serious adverse events in the form of pulmonary toxicities should also be taken into account.